A Bibliometric Analysis of DevOps Metrics - Angarita, Leonardo Bermon; Carpio, Alvaro Fernández Del; Osorio Londoño, Andrés Alberto (DESIDOC Journal of Library & Information Technology, 2023)
DevOps has become an important set of organisational and technical practices in software development under the agile umbrella. Many efforts are still being made in this field, mainly focused on the inclusion of metrics for monitoring progress. Gathering metrics is a difficult task, but it can provide insight into the performance of the software delivery process. The current status of the definition, application and implementation of metrics in DevOps projects and processes is of interest to software practitioners. Thus, the objective of this article is to analyze documents regarding the impact of metrics in DevOps projects. 103 documents were obtained from the Scopus database to analyze them through the bibliometric method considering several aspects. The bibliometric analysis performed included author analysis, author affiliation, authors’ countries, keyword analysis, citation analysis, and network analysis. The results indicate that DevOps research is not centralized in a specific group of researchers. Moreover, the most significant contributions of DevOps are related to continuous integration, software design, and software testing. The bibliometric analysis presented in this article helps to identify the current state of the DevOps literature and provides an insightful discussion of future research trends.